2017
DOI: 10.1097/bot.0000000000000799
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes After Severe Distal Tibia, Ankle, and/or Foot Trauma: Comparison of Limb Salvage Versus Transtibial Amputation (OUTLET)

Abstract: Summary: Severe foot and ankle injuries are complex and challenging to treat, often requiring multiple operations to salvage the limb contributing to a prolonged healing period. There is some evidence to suggest that early amputation for some patients may result in better long-term outcomes than limb salvage. The challenge is to identify the regional injury burden for an individual that would suggest a better outcome with an amputation. The OUTLET study is a prospective, multicenter observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…The findings of this study appear to be consistent with the recently reported results of the Outcomes After Severe Distal Tibia, Ankle, and/or Foot Trauma: Comparison of Limb Salvage Versus Transtibial Amputation trial (OUTLET), a prospective, observational multicentre study of North American civilian patients. 41 , 42 There were 410 patients in the limb salvage group and 87 in the transtibial amputation group who completed the Short Musculoskeletal Function Assessment (SMFA) at 18 months. Patients with reconstructed severe distal tibia, and/or mid- or hindfoot injuries reported significantly poorer scores across most SMFA domains, particularly mobility, compared with those treated with transtibial amputation.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study appear to be consistent with the recently reported results of the Outcomes After Severe Distal Tibia, Ankle, and/or Foot Trauma: Comparison of Limb Salvage Versus Transtibial Amputation trial (OUTLET), a prospective, observational multicentre study of North American civilian patients. 41 , 42 There were 410 patients in the limb salvage group and 87 in the transtibial amputation group who completed the Short Musculoskeletal Function Assessment (SMFA) at 18 months. Patients with reconstructed severe distal tibia, and/or mid- or hindfoot injuries reported significantly poorer scores across most SMFA domains, particularly mobility, compared with those treated with transtibial amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Selecting limb preservation was an essential issue in the present case, although there are currently no established guidelines for deciding between early amputation and reconstruction for severe lower limb injuries. 6 Given that extensive tissue necrosis even involved the osteomyelitis and caused neurological deficits, it was possible that there was no choice but to amputate. However, considering the patient’s young age and the family’s strong desire, we chose limb reconstruction as the desirable therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
“…These "parent" studies included 3 studies of very severe, limb-threatening tibia fractures and amputations (FIXIT, OUTLET, and TAOS), 2 studies of slightly less severe lower-limb fractures (OXYGEN and VANCO), and 1 study of isolated, low severity fractures (Pain) all of which have been completed and previously described. [15][16][17][18][19][20] The key characteristics of these studies are shown in Supplemental Digital Content (see Table 1, http://links.lww.com/JOT/B602).…”
Section: Study Participantsmentioning
confidence: 99%